Epidemic Zika virus strains from the Asian lineage induce an attenuated fetal brain pathogenicity - Maïlis Darmuzey; Franck Touret; Emily Slowikowski; Ivan Gladwyn-Ng; Karan Ahuja; Lorena Sanchez-Felipe; Xavier de Lamballerie; Catherine Verfaillie; Pedro E. Marques; Johan Neyts; Suzanne J. F. Kaptein (Nature Communications)
Abstract The 2015–2016 Zika virus (ZIKV) outbreak in the Americas revealed the ability of ZIKV from the Asian lineage to cause birth defects, generically called congenital Zika syndrome (CZS). Notwithstanding the long circulation history of Asian ZIKV, no ZIKV-associated CZS cases were reported prior to the outbreaks in French Polynesia (2013) and Brazil (2015). Whether the sudden emergence of CZS resulted from an evolutionary event of Asian ZIKV has remained unclear. We performed a comparative analysis of the pathogenicity of pre-epidemic and epidemic Asian ZIKV strains in mouse embryonic brains using a female immunocompetent intraplacental infection mouse model. All studied Asian ZIKV strains are neurovirulent, but pre-epidemic strains are consistently more pathogenic in the embryos than their epidemic equivalents. Pathogenicity is not directly linked to viral replication. By contrast, an influx of macrophages/microglial cells is noted in infected fetal brains for both pre-epidemic and epidemic ZIKV strains. Moreover, all tested ZIKV strains trigger an immunological response, whereby the intensity of the response differs between strains, and with epidemic ZIKV strains generally mounting a more attenuated immunostimulatory response. Our study reveals that Asian ZIKV strains evolved towards pathogenic attenuation, potentially resulting in CZS emergence in neonates rather than premature death in utero.